Regional needs assessment for emergency physician audit and feedback. Issue 4 (July 2020) - Gupta, Rakesh; Mercuri, Mathew; McCulloch, Amy; Monteiro, Sandra; Mastoras, George; Krywenky, Ashley; Chan, Teresa; Mondoux, Shawn
ABSTRACT: Objectives: Audit and feedback is widely used to improve physician performance. Many data metrics are being provided to physicians, yet most of these are driven by the regulatory environment. We sought to conduct a needs assessment of audit and feedback metrics that were most useful to clinicians within our health care region. Methods: We conducted a Web-based survey of five clinical practice sites in our region and asked that physicians rank 49 clinical practice metrics. In addition, we assessed their readiness for audit and feedback and their preferences for data confidentiality. We collected data on duration of training, gender, and site of practice (academic v. community) allowing for comparison between groups. Results: A total of 104 emergency medicine physicians participated in the survey (52.3% response rate). There was a significant readiness for participation in audit and feedback activities. Top ranked metrics were emergency department return rates and colleague's assessment of collegiality and quality of care, which were common across all sites. Small yet significant differences were noted between genders and academic v. community practitioners. Conclusion: This study represents the first regional analysis of physician preferences for audit and feedback activities and implementation. It demonstrates that physicians are interested in audit and feedback activities and provides a roadmap for the development of a regional audit and feedback structure. It will also be used as a guiding document for regional change management.